A review of potential factors contributing to epidemic novel coronavirus (SARS-COV-2) in China - Ali Al-Maqtariab, Qais; Al-Gheethic, Adel; Ali Mahdib, Amer; Al-Ansib, Waleed; Nomand, Efaq (Penerbit UTHM, 2020)
The pandemics of zoonotic coronaviruses have been detected frequently in the current decade. At the moment novel coronavirus (SARS-COV-2) is causing pandemics in China. Among numerous factors which impact on the occurrence of viral infections in human, the cultural practices, high population, and food habits are most related. Therefore, the virus's genetic sequence and initial data on the epidemiology and clinical symptoms of 2019-nCoV infections are only the first steps to understanding the threat posed by the virus. In contrast, the factors contributing to epidemic SARS-COV-2 should be investigated more to refine the risk evaluation of SARS-COV-2 pandemic and ensure the prevention of a similar disease in the future.